Flexible percutaneous endoscopic retroperitoneal necrosectomy as rescue therapy for pancreatic necroses beyond the reach of endoscopic ultrasonography: A case series. Issue 3 (20th March 2017) - Jürgensen, Christian; Brückner, Stefan; Reichel, Stephanie; Kilian, Maik; Pannach, Sven; Distler, Marius; Weitz, Jürgen; Neser, Frank; Hampe, Jochen; Will, Uwe
Abstract : Minimally invasive or endoscopic transluminal drainage and necrosectomy are the standard of care for infected pancreatic fluid collections and necroses after pancreatitis. In an endoscopic treatment algorithm, necroses beyond the reach of safe endoscopic access are typically treated by percutaneous drainage. We aimed to evaluate percutaneous minimally invasive necrosectomy using a purely endoscopic technique in patients with extensive necrosis. In patients with necroses beyond safe transluminal reach, the percutaneous drainage canal was used for flexible endoscopic access and dilatation of the tract to 20 mm. Percutaneous endoscopic necrosectomy was carried out through this canal. We present a case series of 14 patients in whom between one and four necrosectomy (median two) sessions were done to remove solid necroses successfully in 13 out of 14 patients. There were no major complications apart from one patient with abdominal compartment syndrome secondary to delayed erosion of the splenic artery. Percutaneous flexible necrosectomy might evolve into an alternative to surgical minimally invasive necrosectomy in anatomical sites beyond transluminal endoscopic reach.